Blackness and Heathenism. Color, Theology, and Race in the Portuguese World, c. 1450-1600 (2016)
The coexistence of a process of hierarchy and discrimination among human groups alongside dynamics of cultural and social hybridization in the Portuguese world in the early modern age has led to an intense historiographical debate. This article aims to contribute to extending our perspectives, focusing on the circulation of two global categories of classification: negro (Black) and gentio (Heathen) between the mid-fifteenth and late-sixteenth century. In particular, it explores the intersections between the perception of skin color and the reworking of theological concepts in a biologizing direction, which ran parallel to the development of an anti-Jewish theory based on blood purity. The line of enquiry leads from the coasts of West Africa, where it immediately meets the problem of slavery, to Brazil, via South Asia. The intense cross-fertilization of the categories of negro and gentio in the Portuguese world provides us with an alternative geography and institutional process of racialization to that of the Spanish Empire.